HISPIDULIN AND OTHER CONSTITUENTS OF SCOPARIA DULCIS LINN (Journal of Science and Technology, 2016)
Phytochemical investigation of the ethanol extract of the whole plant of Scoparia dulcis, has resulted in the isolation of 4, 5, 7-trihydroxy-6-methoxyflavone, commonly called hispidulin and a steroidal glycoside, β-sitosterol-β-D-glucoside.  This is the first isolation of the two compounds from S. dulcis. Also isolated and characterized were the previously reported 6-me-thoxybenzoxazolinone, friedelan-3-one and scopadulcic acid B. Structural elucidation was done on the basis of spectroscopic data interpretations (IR, UV, NMR and EIMS).  Using the Tetrazolium-based colorimetric selective assay, hispidulin was found to be inactive against HIV-1/IIIB in MT-4 cells whereas the same test on the aqueous extract of the plant was positive.